The Effect of Government Expenditure in Education, Health and Social Assistance Spending on the Poverty Rate of Yogyakarta Special Region Province - Muhamad Khisanul Fakhrudin Akbar; M Taufiq (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study has the final results to determine the relationship between government spending in education, health and social assistance spending on poverty rates in the Special Region of Yogyakarta. This secondary data-based research has the form of a time series in 2012-2021, then the method used is multiple linear regression analysis with the OLS (Ordinary Least Squares) method. The results showed that programs on education implemented by the government of the Special Region of Yogyakarta through variable government spending in education were right on target and able to reduce poverty. but, variable government spending on health has not been able to reduce poverty and social assistance spending will increase poverty due to the effects of government dependence.